PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DIVISI QIP PT. GSI CIANJUR - Suharyanto, Suharyanto; Nugraha, Ery; Permana, Hendra (Jurnal Ilmiah Teknik Industri, 2014)
The role of human resource management is continously improved to enhance the performance of employees. PT GSI, as one of Indonesian company producing shoe products to meet demand from all around the world, needs employees with high performance. On the other side, the employees need reasonable compensation and safe work environments. This research is conducted to investigate the relationships and the effects of the compensation and work environment variables on the job performance. Using causal descriptive research method, samples of 77 units are randomly taken from 328 labors at the Quality Inspection Production Divison. The questionaire comprising eighteen questions is applied to explore the employee minds and perceptions on the relationships and effects of the compensation and work environment variables toward the job performance variable. The result of this research shows that compensation (X1) and work environment (X2) variables simultanously effect to the job performance variable (Y). The linier regression equation constructed is represented by Y = 4,375 - 0,181X1 + 0,382X2.